'Mayacene' floodplain and wetland formation in the Rio Bravo Watershed of northwestern Belize. (October 2015) - Beach, Tim; Luzzadder-Beach, Sheryl; Krause, Samantha; Walling, Stanley; Dunning, Nicholas; Flood, Jonathan; Guderjan, Thomas; Valdez, Fred
This is the first article to characterize the soil and fluvial geomorphology of the Rio Bravo's fluviokarst watershed in the Rio Bravo Conservation and Management Area, northwestern Belize. Although the watershed has had little-altered tropical forest cover since c . 1000 BP, humans inhabited it for millennia, especially during the Maya Preclassic and Classic, c . 3000–1000 BP. We studied soils and floodplain formation in four excavation transects in the Rio Bravo to understand long-term human impacts on this watershed. Archaic to Preclassic ( c . 3000–1700 BP) sedimentation rates ranged from 0.82 mm yr −1 at Chawak But'o'ob to 1.5 mm yr −1 on the Gran Cacao floodplain. The late Preclassic through Classic ( c . 2300–1000 BP) rates rose 0.98–2.03 mm yr −1, and the Classic ( c . 1700–1000 BP) rates ranged from 1 mm yr −1 to as high as 9.12 and 16.27 mm yr −1 at ancient Maya wetland field sites. Post Classic rates dropped back in the one dated profile, and the well-developed topsoils indicate long-term surface stability. Older soils at the edges and higher islands of the valley had more vertic features and full Vertisols, whereas Vertic Mollisols and Aquerts have formed in younger sediments. We also present new evidence for late Classic Maya wetland field formation at Chawak But'o'ob, which shows field raising with canalization in this wetland of low ionic water. All the soil profiles with dating and stable carbon isotope evidence exhibited increased δ 13 C in the profiles through the Classic period sediments, although some were equivocal. The two wetland field δ 13 C profiles through the Classic period sediments increase by c . 6‰ at Chawak But'o'ob and 3‰ at the Birds of Paradise (BOP) Field center, although earlier BOP profiles increased by as much as 7‰. Hence, this watershed exhibits three large diachronic shifts: from lower to higher and again to lower deposition over pre-Maya, Maya, and post-Maya times. These changes along with earlier evidence for ancient intensive agriculture from 3000 and 1000 BP lie sandwiched between the ancient and contemporary little-altered tropical forest.